(3ChbGa GdcaQs ((3CMeO QaYJ s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje ai HjGf ChbGa GdcaQ hgj SHYI YTQ ehVY Ef cGf YGdekG caQ ShOG cGf ai GdUdGI Ch NGQLgG hEf cGf LGgdkG jYPQ s
(3BNQgG (B:s
(3hEf cGfJ SHYI YTQ ai hGdJjf ai CSad SGadjf Ke jHJOF EdG GdPjf fbdJ ef aJGhi GdedJbW hGddg CYde JeJ s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdbQGAGJ hGdJLhjOs